The relationship between liquidity risk and performance of banking system in Malaysia / Nur Arrdilla Arastam @ Rustam - Arastam @ Rustam, Nur Arrdilla (2019)
This paper objective to examine the relationship between liquidity risk and performance of banking system in Malaysia, using the measurement of Funding Liquidity Risk, Liquid Asset Ratio for liquidity risk and the profitability of the banks for the performance. The result found out that there is significant relationship between both variables based on the fixed effect regression, the sample of this paper consist of 10 public listed banks in Kuala Lumpur Stock Exchange for the period of 2009 until 2018 which is 10 years period.